Sistem Instalasi Pembangkit Pikohidro Untuk Keluaran Listrik Arus Searah 12 Volt - Andrik Sunyoto; Priya Surya Harijanto; Bakti Indra Kurniawan (Elposys: Jurnal Sistem Kelistrikan, 2022)
This research is focused to help peoples in remote areas who do not have electricity supply from PLN, but have sources of water flow in rivers. The main objective of this research is to create a picohydro hydroelectric power plant with a floating turbine to utilize the kinetic energy of river water flow in areas that have not been supplied with PLN electricity. The flow of water in the river will rotate the turbine, which in the end the rotational power is channeled through a pulley and belt system, which eventually turns an alternator. The alternator used is a three-phase AC alternator. Then the AC current will be rectified by the bridge rectifier to then be used to charge the battery and go to the load. In addition, in this study, the ability of the pico-hydro system to supply electrical energy will be tested to be able to run 12 V DC electrical loads and charge 12 V batteries.